2019
DOI: 10.1007/s10143-019-01182-5
|View full text |Cite
|
Sign up to set email alerts
|

Obesity paradox in subarachnoid hemorrhage: a systematic review

Abstract: As the number of obese people is globally increasing, reports about the putative protective effect of obesity in life-threatening diseases, such as subarachnoid hemorrhage (SAH), are gaining more interest. This theory-the obesity paradox-is challenging to study, and the impact of obesity has remained unclear in survival of several critical illnesses, including SAH. Thus, we performed a systematic review to clarify the relation of obesity and SAH mortality. Our study protocol included systematic literature sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 46 publications
0
22
1
Order By: Relevance
“…As we previously mentioned, obesity predisposes an increased risk of suffering cardiovascular and systemic diseases, such as stroke and other diseases. 29,33,34,[47][48][49] It is associated with premature mortality; and, in multiple studies, a higher risk of cardiovascular disease incidence has been demonstrated in underweight adults or just overweight (but not obese) patients. As a result, there is no clear evidence of a higher prevalence or incidence of stroke in those with an obesity diagnosis.…”
Section: The Obesity Paradoxmentioning
confidence: 99%
“…As we previously mentioned, obesity predisposes an increased risk of suffering cardiovascular and systemic diseases, such as stroke and other diseases. 29,33,34,[47][48][49] It is associated with premature mortality; and, in multiple studies, a higher risk of cardiovascular disease incidence has been demonstrated in underweight adults or just overweight (but not obese) patients. As a result, there is no clear evidence of a higher prevalence or incidence of stroke in those with an obesity diagnosis.…”
Section: The Obesity Paradoxmentioning
confidence: 99%
“…The two largest studies were based on patient registries yielding considerable case numbers but came to diverging results with one trial documenting reduced in-hospital mortality and the other rejecting the obesity paradox [6,10]. The methodological integrity of these trials was critically addressed in a recent systematic review [27]. It remains possible that a protective effect of mild obesity exists -unspeci c to SAH or stroke -potentially related to overall caloric reserves which may prove advantageous in the light of long ICU stays [18,23].…”
Section: Discussionmentioning
confidence: 99%
“…A single trial in SAH patients described a lower risk of DCI and DCI-related infarction associated with elevated BMI [29]. Nonetheless, the results of a systemic review addressing this obesity paradox in SAH remained inconclusive as most trials suffered restrictions in design, resulting in limited external validity [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, hypercholesterolemia was associated with a seemingly paradoxical 40% reduction in the risk of aSAH in a review of case-control studies [12]. Furthermore, a recent systematic review on obesity and aSAH indicated a reduced risk of aneurysm rupture with increasing BMI but concluded that this seemingly paradoxical relation remains to be studied in more detail [33]. The same group performed a systematic review on cholesterol as a risk factor for aSAH and concluded that elevated TC levels increased the risk of aSAH among men [26].…”
Section: Introductionmentioning
confidence: 99%